Liability in medical negligence: looking into the position of non-medical staff / Nur Azura Othman, Mohd Azali Ibrahim and Tengku Chik Abu Bakar Tengku Ibrahim - Othman, Nur Azura; Ibrahim, Mohd Azali; Tengku Ibrahim, Tengku Chik Abu Bakar (2006)
Due to the increasing numbers of population and changes of environment, people are more exposed towards certain diseases. Through this exposure, it will surely affect the duty of a doctor by which the numbers of patients will growth instantly. With the numbers of doctors that we have in our country nowadays, it is impossible for the doctors to fully utilize the needs of a patient without having delegates their duties to another staffs. The delegation of the work normally been carried out by the nurses, pharmacist and other person related to that profession. However, through this delegation, it can make the doctors be sued by the patients if any negligent act committed by the other staffs other than the doctors' own act. This is because, patients will straightly proceed to sue the doctors without having notice that the act committed was not the doctor's fault and the presumption is that the doctors should be fully responsible for whatever happened to them. Thus, through this project paper, we will discuss the duty of doctors and each staffs and their liabilities. As a result, people will be aware about the existence of duty of staffs apart from doctor's duty. Therefore, this project paper had suggested certain recommendations as a solution in order to ensure that the doctors are not fully liable for the negligent act committed by the other staffs.